Serum CXCL9 and CXCL10 as Emerging Biomarkers in Ocular Toxoplasmosis: Bridging Inflammation and Diagnostic Precision - putra, prasaundra triantoni; Sofia, Ovi; Fitri, Loeki Enggar (International Journal of Retina, 2026)
Ocular toxoplasmosis (OT), the most prevalent cause of posterior uveitis worldwide, frequently results in severe visual impairment due to infections to Toxoplasma gondii. Chemokines CXCL9 and CXCL10, induced by interferon-gamma (IFN-γ), are key mediators in directing T cells and monocytes to infected ocular tissue. This review synthesizes current evidence on the role of serum CXCL9 and CXCL10 in OT pathogenesis, highlighting their involvement in immune cell trafficking, the CXCR3 receptor pathway, and the balance between host defense and retinal damage. We critically examine differences in chemokine levels between acute and chronic phases, as well as their correlation with disease activity, across human and experimental studies. Additionally, their potential as biomarkers for diagnosis and monitoring in both congenital and acquired OT is discussed. Elevated serum levels during active infection suggest clinical relevance, warranting further investigation through longitudinal and mechanistic studies to guide future therapeutic strategies.